Intermediate care units in progressive patient care model: a systematic literature review (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Progressive patient care (PPC) has been defined as a systematic classification and segregation of patients based on their medical and nursing needs. Aim of the present research was to perform a systematic literature review about existing medical intermediate care unit organizational models and their performance strengths and weaknesses with a specific focus on Italian implementation, respect to US model.Methods: Databases PubMed, Cinahl, Google and Google Scholar were searched until September 2017. The search was limited to Italian and English studies. All study design are included in the review.Results: Ten studies were included in the review. The American studies showed, after the PPC reorganization, an increase in level of satisfaction and nursing care, a reduction in average length of stay, costs and tensions between nurses and an improvement in nurse-physician communication. An Italian study reported the results of a project carried out in three case studies (Forlì, Foligno and Pontedera hospital), redesigning hospital patient flow logistics around the concept of intensity of care: in all three cases, after the reorganization, an increase in bed occupancy rate (before: 71%,81%,65%; after: 78%,84%,82%, respectively) and in hospital case-mix complexity (average DRG weight - before: 0.99,1.07,1.12; after: 1.19,1.09,1.61, respectively) and a reduction in turn-over ratio (before: 2.5,1.4,2.8; after: 1.5,1.2,1.7, respectively) was recorded. Considering Italian healthcare professionals’ point of view, majority of internists supported a hospital remodeling according to PPC model.Conclusions: The PPC model, theorized in US, has found several applications in Italian regional realities. Improvements in quality of care, appropriateness and productivity in healthcare facilities, that adopted the PPC program, were observed.